Doing Networked Learning Research with AI: Creation and Interpretation - Lee, Kyungmee; Lacković, Nataša; Bonderup Dohn, Nina (Proceedings of the International Conference on Networked Learning, 2026)
Generative AI is rapidly becoming part of networked learning environments—but how should we research learning when AI itself participates in meaning-making, interpretation, and analysis? This workshop invites researchers to move beyond seeing AI as a simple tool and instead engage with it as a methodological and epistemic collaborator. Through hands-on activities using generative AI for visual elicitation, qualitative analysis, and interpretive experimentation, participants will explore what it means to do networked learning research with AI. The workshop is designed for researchers who want practical methods, critical perspectives, and concrete ideas they can take back to their own qualitative projects—no technical expertise required, just curiosity and a willingness to rethink agency, data, and interpretation.